Aberrant Transforming Growth Factor‐β Activation Recruits Mesenchymal Stem Cells During Prostatic Hyperplasia. (7th September 2016) - Wang, Long; Xie, Liang; Tintani, Francis; Xie, Hui; Li, Changjun; Cui, Zhuang; Wan, Mei; Zu, Xiongbing; Qi, Lin; Cao, Xu
Abstract: Benign prostatic hyperplasia (BPH) is the overgrowth of prostate tissues with high prevalence in older men. BPH pathogenesis is not completely understood, but it is believed to be a result of de novo overgrowth of prostatic stroma. In this study, we show that aberrant activation of transforming growth factor‐β (TGF‐β) mobilizes mesenchymal/stromal stem cells (MSCs) in circulating blood, which are recruited for the prostatic stromal hyperplasia. Elevated levels of active TGF‐β were observed in both a phenylephrine‐induced prostatic hyperplasia mouse model and human BPH tissues. Nestin lineage tracing revealed that 39.6% ± 6.3% of fibroblasts and 73.3% ± 4.2% smooth muscle cells were derived from nestin + cells in Nestin‐Cre, Rosa26‐YFP flox/+ mice. Nestin + MSCs were increased in the prostatic hyperplasia mice. Our parabiosis experiment demonstrate that nestin + MSCs were mobilized and recruited to the prostatic stroma of wild‐type mice and gave rise to the fibroblasts. Moreover, injection of a TGF‐β neutralizing antibody (1D11) inhibits mobilization of MSCs, their recruitment to the prostatic stroma and hyperplasia. Importantly, knockout of TβRII in nestin + cell lineage ameliorated stromal hyperplasia. Thus, elevated levels of TGF‐β‐induced mobilization and recruitment of MSCs to the reactive stroma resulting in overgrowth of prostate tissues in BPH and, thus, inhibition of TGF‐β activity could be a potential therapy for BPH. Stem Cells Translational Medicine 2017;6:394–404